Efforts Of Lasi Character In Identity Control In Ahmad Tohari's Bekisar Merah Novel - Maydita, Sabrina Rizki; Supriyanto, Teguh (Universitas Negeri Semarang, 2021)
This study aims to analyze the efforts of the Lasi character in fighting for his identity, and why it was fought for. This research is a qualitative research that uses a sociological literature approach. The data source of this research is the text of the novel Bekisar Maerah by Ahmad Tohari, published by PT Gramedia Pustaka Utama, in Jakarta in 2013. The data in this study are fragments of the novel Bekisar Merah by Ahmad Tohari which allegedly contain identity. The research results are as follows; 1) the Lasi figure found in fighting for his identity, 2) found the identity that Lasi was fighting for, namely self-identity and social identity, 3) found three reasons why Lasi struggled for her identity. First, because of her dignity as a woman. Second, because Lasi upheld the teachings of her mother. Third, because of love and loyalty to her husband.